2013
DOI: 10.1111/gfs.12058
|View full text |Cite
|
Sign up to set email alerts
|

α‐Tocopherol and β‐carotene contents of forage species in a four‐cut system

Abstract: α‐Tocopherol and β‐carotene concentrations were measured in herbage of birdsfoot trefoil (Bft), red clover (Rc), white clover (Wc), timothy (Ti) and perennial ryegrass (Pr) grown in four mixtures (Bft+Ti, Rc+Ti, Rc+Pr and Wc+Pr) in a small‐plot field experiment at Foulum, Denmark, over 2 years. Plots were fertilized with cattle slurry and harvested in a four‐cut system: 30 May/7 June, 5 July/12 July, 22 August/21 August and 24 October/9 October in 2005/2006. Bft was the legume with the highest α‐tocopherol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Sickel et al 18 observed an average total tocopherol concentration of 141 mg/kg DM in mountain plant species. Graulet et al 17 reported an average α-tocopherol concentration of 256 mg/kg DM in mountain plant species, whereas a concentration below 50 mg/kg DM was observed by Elgersma et al 19 and Lindqvist et al 20 in lowland areas. Concentrations of γ-tocopherols were in the range of values reported by Sickel et al 18 but lower than values observed by Graulet et al 17 Kalber et al 31 measured the tocopherol contents of buckwheat and phacelia when mixed with ryegrass and surprisingly found values 10 times lower than values obtained in this study.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Sickel et al 18 observed an average total tocopherol concentration of 141 mg/kg DM in mountain plant species. Graulet et al 17 reported an average α-tocopherol concentration of 256 mg/kg DM in mountain plant species, whereas a concentration below 50 mg/kg DM was observed by Elgersma et al 19 and Lindqvist et al 20 in lowland areas. Concentrations of γ-tocopherols were in the range of values reported by Sickel et al 18 but lower than values observed by Graulet et al 17 Kalber et al 31 measured the tocopherol contents of buckwheat and phacelia when mixed with ryegrass and surprisingly found values 10 times lower than values obtained in this study.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Indeed, the total tocopherol concentration was not correlated with leaf proportions (r = −0.015, P = 0.92), and species with larger leaves such as crimson clover contained less tocopherol than species with small-sized leaves such as vetch. Lindqvist et al 20 explained the higher α-tocopherol content in birdsfoot trefoil compared with red clover by a slower growth rate and fewer actively growing leaves. However, in the present study, crimson clover was the plant species with the lowest tocopherol content but not the plant species with the shortest growth period.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hay yield (t ha -1 ) for those samples were calculated by drying approximately 500 g samples at 55 °C for 48 hour followed by storage for a further day at room temperature (Ates and Tekeli, 2007;Ateş and Seren, 2020). Besides, 600 g fresh herbage samples (Lindqvist et al 2013) of the field pea genotypes were taken from each plot at all growth stages at 3 cm height from ground level before ergocalciferol analyses. Then, samples were sterilized in 2 % sodium hypochlorite solution for 15 minute and washed in distilled water three times (Bajji et al 2002;Tenikecier and Ates, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Then, samples were sterilized in 2 % sodium hypochlorite solution for 15 minute and washed in distilled water three times (Bajji et al 2002;Tenikecier and Ates, 2018). The samples in sterile plastic bag for ergocalciferol analyses were frozen (-20 °C) immediately after sterilized (Lindqvist et al 2013). The ergocalciferol contents (µg kg -1 in fresh matter (FM) basis) of freeze-dried samples were determined according to the methods described by Jäpelt et al (2011).…”
Section: Methodsmentioning
confidence: 99%